Working mothers’ involvement in children's preschool education in Malaysia - Singh, Gurdip Kaur Saminder; Ghani, Yunera Carlyna K. (Edelweiss Applied Science and Technology, 2025)
As more women join the workforce to meet survival demands, understanding their challenges in raising young children, especially in education, is vital. This qualitative study, which used a phenomenological approach, was designed to explore the experiences of 31 working mothers through in-depth interviews to uncover the dynamics of maternal involvement in preschool education. Thematic analysis with three-cycle coding revealed five key themes, highlighting the complexities mothers face in balancing professional responsibilities with active support for their children’s early learning. Findings indicated that there is consensus that maternal involvement at the preschool education level serves as a crucial foundation for children to excel academically prior to primary education. However, there seems to be a disconnect between mothers' understanding of support and the expectations of educational institutions regarding parental involvement in education. Findings also highlighted that although working mothers apply various adaptive approaches to balance professional responsibilities with academic support for their children, they seriously struggle to balance career aspirations with familial responsibilities. These findings offer valuable insights for educators, policymakers, and employers seeking to establish environments that support the holistic development of children while acknowledging and alleviating the challenges faced by working mothers, creating a broader community impact on gender equity.